Модель функціонального діагностування енергоефективності асинхронного електропривода - Закладний, Олег Олександрович; Закладний, Олександр Миколайович; Чермалих, Валентин Михайлович (НТУ "ХПІ", 2013)
In this article described the model of functional diagnostics of energy efficiency, energy consumption and energy use processes of the asynchronous electric drive, and the results of analytical test model for induction motors, new industrial series 5A.
Model of functional diagnostics of energy efficiency of asynchronous electric drive
Keywords: електромеханічні системи; рівень енергоспоживання; енергетичний менеджмент; параметри енергоефективності